2013
DOI: 10.3109/08880018.2013.774450
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Borderline Tumors in Pre-Menarche Girls

Abstract: By reason of a new case of an ovarian mucinous borderline tumor (BOT) in a pre-menarche girl, a research of current literature was implemented. Low-grade malignant epithelial tumors are extremely rare in young children and, as far as we know, only a few case reports exist. The patients presented with vomiting, pain, and a swollen lower abdomen. Pre-operative diagnosis primarily consists of imaging techniques. At Stage Ia, the tumor is confined to the ovary without penetration of the capsule, no malignant ascit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(46 reference statements)
0
1
0
2
Order By: Relevance
“…Radiológicamente, los BOT son una masa anexial compleja, multilobulada con elementos sólidos en su interior (nódulos redondos bien diferenciados, con proyecciones papiliformes o engrosamiento de la pared). La literatura reporta que los nódulos y el grosor de los septos son más grandes en tumores malignos que en los BOT, sin embargo es difícil diferenciar por resonancia magnética los tumores borderline de los tumores invasivos malignos en etapa temprana 4,13 . Se ha logrado mejorar la diferenciación con medio de contraste, no obstante, la información es limitada.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Radiológicamente, los BOT son una masa anexial compleja, multilobulada con elementos sólidos en su interior (nódulos redondos bien diferenciados, con proyecciones papiliformes o engrosamiento de la pared). La literatura reporta que los nódulos y el grosor de los septos son más grandes en tumores malignos que en los BOT, sin embargo es difícil diferenciar por resonancia magnética los tumores borderline de los tumores invasivos malignos en etapa temprana 4,13 . Se ha logrado mejorar la diferenciación con medio de contraste, no obstante, la información es limitada.…”
Section: Discussionunclassified
“…Se estima que más de 200,000 mujeres desarrollan cáncer de ovario cada año en el mundo. En el caso de los tumores malignos primarios, el 70% son de origen epitelial y de estos, un 20% de bajo potencial maligno, denominados BOT 4 .…”
Section: Introductionunclassified
“…1 This type of disease is rare in adolescents, representing 10 to 30% of epithelial tumors and less than 1% of all ovarian masses in the period between 12 and 18 years of age. [2][3][4][5][6][7] A recent systematic review has found only 300 cases of borderline ovarian tumors (BOTs) in the literature. 8 The identification of a BOT during pregnancy in an adolescent patient is much more uncommon and may represent a real diagnostic challenge.…”
mentioning
confidence: 99%